In-situ polymerized 2D confined nanocomposite for visual enantioselective recognition - Qing Xu; Yi-Han Wen; Long Yi Jin; Hui-Yu Zhao; Yi-Rong Pei (Applied Clay Science, 2026)

Carbon dot-based catalytic materials: From photo/electrocatalysis to nanozyme activity - Pei-De Zhu; Chang Liu; Hui Wang; Rong-Yu Yao; Ling-Rui Sun; Xin-Ru Xu; Jing-Wen Jiang; Ying-Sheng Xu; Kun-Peng Lin; Jia-Xing Wu (Journal of Environmental Chemical Engineering, 2026)

Effects of nitrogen and phosphorus limitation on physiological regulation and Sulfur cycling dynamics in Symbiodiniaceae - Yu-Rong Zheng; Yu-Chien Kao; Chun-Ting Chen; Chih-Chung Yen; Nilubol Nuanjunkong; Guang-Yuh Jauh; Pei-Luen Jiang (Journal of Experimental Marine Biology and Ecology, 2026)

Synthesis and production of hydroxytyrosol derivatives with potent anti-inflammatory activities - Te-Sheng Chang; Wen-Yueh Ho; Jiumn-Yih Wu; Chien-Yu Wu; Pei-Rong Cai; Bo Eng Cheong; Wilson Thau Lym Yong; Peik Lin Teoh (Natural Product Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Ion-specific multiscale regulation of gelatinization and retrogradation in normal and waxy wheat starches: Cooperative roles of valence, hydration, and molecular chain architecture - Tian Lv; Xin-rong Lv; Shu-ning Yuan; Yu Hu; Rong-ran Zhang; Yue Zhang; Chuan Zhong; Pei Wang; Qin Zhou; Dong Jiang; Hao Jiang; Tao Yang (Food Hydrocolloids, 2026)

Risk assessment and environmental influencing factors of urinary polycyclic aromatic hydrocarbons metabolites in pregnant women in Zunyi, China - Jing Yang; Jing Jiang; Linfei Wu; Pei Xu; Nian Wu; Rui Yu; Yanling Xiao; Xingting Zheng; Rong Zeng; Yuanzhong Zhou; Yan Xie; Xubo Shen (Journal of Environmental Sciences, 2026)

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

Assessing 3-D variability of ultrafine particle using a Geo-AI modelling approach: A case study in Zhunan-Miaoli, Taiwan - Chia-Wei Hsu; Yinq-Rong Chern; Jun-Jun Su; Pei-Yi Wong; Aji Kusumaning Asri; Candera Wijaya; Yu-Cheng Chen; Shih-Chun Candice Lung; Ta-Chih Hsiao; Tee-Ann Teo; Yi-Liang Shih; Chih-Da Wu (Environmental Pollution, 2025)

Cytochrome P450-mediated biotransformation of octocrylene in Tetradesmus obliquus: Integrative insights from transcriptomics, proteomics, molecular docking, and density functional theory calculation - Jun-Jie Hu; Chang-Gui Pan; Xiang-Rong Xu; Feng-Jiao Peng; Shan Liu; Jiying Pei; Zhen-Zhu Liu; Hao Liang; Kefu Yu (Journal of Hazardous Materials, 2025)

Implementation and topological characterization of Weyl exceptional rings in quantum-mechanical systems - Hao-Long Zhang; Pei-Rong Han; Xue-Jia Yu; Shou-Bang Yang; Jia-Hao Lü; Wen Ning; Fan Wu; Qi-Ping Su; Chui-Ping Yang; Zhen-Biao Yang; Shi-Biao Zheng (Science Bulletin, 2025)

Single and joint associations of exposure to polycyclic aromatic hydrocarbons with hypertensive disorders of pregnancy: A nested case-control study - Rui Yu; Cheng Chen; Mingyu Deng; Nian Wu; Yanling Xiao; Songlin An; Lin Tao; Xingting Zheng; Jing Yang; Zhongmei Hu; Pei Xu; Xingyan Liu; et al. (Environmental Pollution, 2025)

Ambient air pollution and the risk of cancer: Evidence from global cohort studies and epigenetic-related causal inference - Dong Peng; Xiao-Yu Liu; Yuan-Hui Sheng; Si-Qi Li; Dan Zhang; Bo Chen; Pei Yu; Zhao-Yuan Li; Shuai Li; Rong-Bin Xu (Journal of Hazardous Materials, 2025)

Synergistic properties of single-component hexagonal iron borate for superior and sustainable photo-Fenton catalysis - Po-Yi Wu; Jing-Cheng Hsu; Tsung-Yueh Lin; Yu-Lun Zhu; Yu-Rong Chang; Pei Yuin Keng (Journal of Environmental Chemical Engineering, 2025)

Accumulation of lipophilic and proteinophilic halogenated organic pollutants (HOPs) in the different types of feathers of laying hens - Xi Chen; Xiao-Jun Luo; Qun-Jie Feng; Yu Liu; Jun-Zhe Dai; Peng-Peng Chen; Pei-Xin Su; Qing-Rong Yang; Yan-Hong Zeng; Bi-Xian Mai (Journal of Hazardous Materials, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Trade-offs of reproductive growth and Cd remobilization regulated Cd accumulation in wheat grains (Triticum aestivum L.) - Ying Wang; Pei-Pei Gao; Yu-Meng Shang; Rong-Rong Jia; Yu-Cheng Wang; Xiang-Yu Li; Li-Ping Geng; Yong Zhao; Joshua Walrath; Wen-Ju Liu (Journal of Hazardous Materials, 2024)

Climate change-induced impacts on PM2.5 in Taiwan under 2 and 4 °C global warming - I-Chun Tsai; Pei-Rong Hsieh; Huang-Hsiung Hsu; Yu-Shiang Tung; Yung-Ming Chen; Chao-Tzuen Cheng (Atmospheric Pollution Research, 2024)

In vitro and in vivo protective potential of quercetin-3-glucuronide against lipopolysaccharide-induced pulmonary injury through dual activation of nuclear factor-erythroid 2 related factor 2 and autophagy - Pei-Rong Yu; Chiao-Yun Tseng; Cheng-Chin Hsu; Jing-Hsien Chen; Hui-Hsuan Lin (Archives of Toxicology, 2024)

Over-expression of UDP-glycosyltransferase UGT353G2 confers resistance to neonicotinoids in whitefly (Bemisia tabaci) - Tian-hua Du; Cheng Yin; Lian-you Gui; Jin-jin Liang; Shao-nan Liu; Bu-li Fu; Chao He; Jing Yang; Xue-gao Wei; Pei-pan Gong; Ming-jiao Huang; Hu Xue; et al. (Pesticide Biochemistry and Physiology, 2023)

Properly interpret metabolic inhibition results to identify primary mercury methylating microbes - Pei Lei; Ri-Qing Yu; Yaqi Kong; Stefan Bertilsson; Martin Tsz-Ki Tsui; Tao Jiang; Jiating Zhao; Yu-Rong Liu; Rinklebe Jörg; Huan Zhong (Critical Reviews in Environmental Science and Technology, 2023)

Novel_miR-1517 mediates CYP6CM1 to regulate imidacloprid resistance in Bemisia tabaci (Hemiptera: Gennadius) - Pei-Pan Gong; Xue-Gao Wei; Shao-Nan Liu; Jing Yang; Bu-Li Fu; Jin-Jin Liang; Ming-Jiao Huang; Tian-Hua Du; Cheng Yin; Yao Ji; Chao He; Jin-Yu Hu; et al. (Pesticide Biochemistry and Physiology, 2023)

In-depth profiling of di(2-ethylhexyl) phthalate metabolic footprints in rats using click chemistry-mass spectrometry probes - Yu-Ning Hu; Jin-Tao Zhan; Pei-Rong Bai; Na An; Jun-Jie Tan; Yan-Zhen Wang; Quan-Fei Zhu; Yu-Qi Feng (Journal of Hazardous Materials, 2023)

Molecular Hydrogen Mediates Neurorestorative Effects After Stroke in Diabetic Rats: the TLR4/NF-κB Inflammatory Pathway - Wan-Chao Yang; Ting-ting Li; Qiang Wan; Xin Zhang; Li-Ying Sun; Yu-Rong Zhang; Pei-Chen Lai; Wen-zhi Li (Journal of Neuroimmune Pharmacology, 2023)
Diabetes is an independent risk factor for stroke and amplifies inflammation. Diabetic stroke is associated with a higher risk of death and worse neural function. The identification of effective anti-inflammatory molecules with translational advantages is particularly important to promote perioperative neurorestorative effects. Applying molecular hydrogen, we measured blood glucose levels before and after middle cerebral artery occlusion (MCAO), 48-h cerebral oedema and infarct volumes, as well as 28-day weight, survival and neurological function. We also measured the levels of TLR4, NF-κB p65, phosphorylated NF-κB p65, catecholamines, acetylcholine and inflammatory factors. All measurements comprehensively showed the positive effect and translational advantage of molecular hydrogen on diabetic stroke. Molecular hydrogen improved the weight, survival and long-term neurological function of rats with diabetic stroke and alleviated changes in blood glucose levels before and after middle cerebral artery occlusion (MCAO), but no difference in circadian rhythm was observed. Molecular hydrogen inhibited the phosphorylation of NF-κB and significantly reduced inflammation. Molecular hydrogen mediates neurorestorative effects after stroke in diabetic rats. The effect is independent of circadian rhythms, indicating translational advantages. The molecular mechanism is related to the TLR4/NF-κB pathway and inflammation. Graphical abstract Molecular hydrogen (H 2 ) affects outcomes of ischemic stroke with diabetes mellitus (DM).

Retraction Note: Emerging protective roles of shengmai injection in septic cardiomyopathy in mice by inducing myocardial mitochondrial autophagy via caspase-3/Beclin-1 axis - Yan Cao; Xiaotong Han; Hongwei Pan; Yu Jiang; Xiang Peng; Weiwei Xiao; Jingjing Rong; Fang Chen; Jin He; Lianhong Zou; Yi Tang; Yanfang Pei; et al. (Inflammation Research, 2023)

The effect of isovitexin on lipopolysaccharide-induced renal injury and inflammation by induction of protective autophagy - Chiao-Yun Tseng; Pei-Rong Yu; Cheng-Chin Hsu; Hui-Hsuan Lin; Jing-Hsien Chen (Food and Chemical Toxicology, 2023)

Impacts of 2 and 4°C global warmings on extreme temperatures in Taiwan - I‐Chun Tsai; Pei‐Rong Hsieh; Chao‐Tzuen Cheng; Yu‐Shiang Tung; Lee‐Yaw Lin; Huang‐Hsiung Hsu (International Journal of Climatology, 2023)
Extreme temperatures were considered natural hazards because they could increase morbidity and mortality. Understanding the extreme temperature changes at different warming levels is crucial to climate change mitigation and adoption for human health. This study projected climate change effects on the intensity, occurrence, and duration of extreme temperatures in Taiwan with 2 and 4°C global warming scenarios using the Weather Research and Forecasting model. The future climate simulations were conducted with the pseudo‐global warming approach, and the future climate changes were obtained from the ensemble mean of simulations in the Coupled Model Intercomparison Project 5. The simulated daily mean temperature increased by 1.40 and 3.09°C under 2 and 4°C global warmings. In a warming world, the daily maximum temperature was projected to increase by 1.35–3.00°C, whereas the daily minimum temperature was even higher, leading to weaker diurnal temperature variation in most regions. The simulation results show that intensified heatwaves with frequent and prolonged durations become par for the course, whereas extremely cold days disappear gradually. The occurrence of heatwaves in the future is projected to be five times that in the current climate. Comparing the global warming impacts over different land‐use types, the heatwave occurrence over urban areas rose more quickly than over other land‐use types; forests are less vulnerable to global warming. On the contrary, the changes in extremely cold days over urban areas were weaker than over other land‐use types. Overall, the effects of global warming on temperature revealed that extreme events were more severe with increased temperature than with the mean state of air temperature. Nonlinear behaviours indicated that global warming should be limited to 2°C, and the additional 2°C warming (from 2 to 4°C) should be addressed carefully.

A strategy for screening and identification of new amino acid-conjugated bile acids with high coverage by liquid chromatography-mass spectrometry - Yan-Zhen Wang; Peng-Cheng Mei; Pei-Rong Bai; Na An; Jin-Gang He; Jie Wang; Quan-Fei Zhu; Yu-Qi Feng (Analytica Chimica Acta, 2023)

GDH promotes isoprenaline-induced cardiac hypertrophy by activating mTOR signaling via elevation of α-ketoglutarate level - Zhi-Rong Lin; Zhen-Zhen Li; Yan-Jun Cao; Wen-Jing Yu; Jian-Tao Ye; Pei-Qing Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)

Infestation and distribution of mites on the Yunnan red-backed vole (Eothenomys miletus) in Yunnan Province of southwest China between 2001 and 2015 - Rong Xiang; Xian-Guo Guo; Tian-Guang Ren; Cheng-Fu Zhao; Rong Fan; Zhi-Wei Zhang; Ke-Yu Mao; Pei-Ying Peng; Xiao-Bin Huang; Ti-Jun Qian (Biologia, 2022)

Transcutaneous Auricular Vagus Nerve Stimulation: From Concept to Application - Yu Wang; Shao-Yuan Li; Dan Wang; Mo-Zheng Wu; Jia-Kai He; Jin-Ling Zhang; Bin Zhao; Li-Wei Hou; Jun-Ying Wang; Lei Wang; Yi-Fei Wang; Yue Zhang; et al. (Neuroscience Bulletin, 2021)

MiR-200a with CDC7 as a direct target declines cell viability and promotes cell apoptosis in Wilm’s tumor via Wnt/β-catenin signaling pathway - Xiu-Ling Liang; Yu-Long Wang; Pei-Rong Wang (Molecular and Cellular Biochemistry, 2021)

Relationship Between Body Composition and Balance Performance in Older Adults with Hyperkyphosis - Phunsuk Kantha; Shiow-Chwen Tsai; Chien-Wen Hou; Rong-Sen Yang; Pei-Yu Su; Wei-Li Hsu (Journal of Medical and Biological Engineering, 2021)

The secondary metabolite regulator, BbSmr1 , is a central regulator of conidiation via the BrlA‐AbaA‐WetA pathway in Beauveria bassiana - Jin‐Feng Chen; Yu Liu; Gui‐Rong Tang; Dan Jin; Xi Chen; Yan Pei; Yan‐Hua Fan (Environmental Microbiology, 2021)
Summary The filamentous fungus Beauveria bassiana , an insect fungal pathogen, is widely used for pest biocontrol. Aerial conidia are infectious propagules, and their yield and viability greatly affect the field application of this fungus; however, little is known about the molecular regulatory mechanism of the triggered conidiation. In the present study, we find that the secondary metabolite regulator BbSmr1 is involved in the regulation of asexual conidiation development and stress response in B. bassiana . A deficiency in Bbsmr1 results in a prominent fluffy‐like phenotype on solid medium, decreased conidial yield, accelerated conidial germination, as well as increased tolerance to H 2 O 2 stress and cell wall inhibitors. The deletion of Bbsmr1 also leads to thickened conidial cell walls and changed cell epitopes. Overexpressing either BbbrlA or BbabaA in the ∆Bbsmr1 strain can rescue the phenotypes of conidial development and stress response. BbSmr1 activates BbbrlA transcription by directly binding to the A4GA3 sequence of the BbbrlA promoter. BbBrlA in turn binds to the promoter of Bbsmr1 and negatively regulates the expression of Bbsmr1 . These results indicate that BbSmr1 positively regulates conidial development in B. bassiana by activating the central development pathway BrlA‐AbaA‐WetA and provides insights into the developmental regulatory mechanism of entomopathogenic fungi.

Three pleiotropic loci associated with bone mineral density and lean body mass - Yu-Xue Zhang; Shan-Shan Zhang; Shu Ran; Yu Liu; Hong Zhang; Xiao-Lin Yang; Rong Hai; Hui Shen; Qing Tian; Hong-Wen Deng; Lei Zhang; Yu-Fang Pei (Molecular Genetics and Genomics, 2021)

Two novel pleiotropic loci associated with osteoporosis and abdominal obesity - Lu Liu; Xiao-Lin Yang; Hong Zhang; Zi-Jia Zhang; Xin-Tong Wei; Gui-Juan Feng; Ju Liu; Hui-Ping Peng; Rong Hai; Hui Shen; Qing Tian; Hong-Wen Deng; et al. (Human Genetics, 2020)

Iridoid, phenylethanoid and flavonoid glycosides from Forsythia suspensa - Qian Wei; Rong Zhang; Qin Wang; Xin Jia Yan; Quan Wei Yu; Fu Xia Yan; Chang Li; Yue Hu Pei (Natural Product Research, 2020)

lncRNA H19 sponging miR-93 to regulate inflammation in retinal epithelial cells under hyperglycemia via XBP1s - Rong Luo; Fan Xiao; Pei Wang; Yu-Xiang Hu (Inflammation Research, 2020)

RETRACTED ARTICLE: Emerging protective roles of shengmai injection in septic cardiomyopathy in mice by inducing myocardial mitochondrial autophagy via caspase-3/Beclin-1 axis - Yan Cao; Xiaotong Han; Hongwei Pan; Yu Jiang; Xiang Peng; Weiwei Xiao; Jingjing Rong; Fang Chen; Jin He; Lianhong Zou; Yi Tang; Yanfang Pei; et al. (Inflammation Research, 2020)

De novo transcriptome analysis of an albino mutant Pasphiopedilum pacific shamrock reveals reduced expression of genes related to chloroplast biosynthesis and division - Han Li; Hua Cao; Rong-pei Yu; Zhen Miao; Ji-hua Wang; Su-Ping Qu; Qiang Yuan; Shen-chong Li (Horticulture, Environment, and Biotechnology, 2018)

Metabolic benefits of rivaroxaban in non-valvular atrial fibrillation patients after radiofrequency catheter ablation - Jun Zhu; Rong-jun Gao; Qiang Liu; Ru-hong Jiang; Lu Yu; Ya-xun Sun; Pei Zhang; Jian-wei Lin; Yang Ye; Zu-wen Zhang; Shi-quan Chen; Hui Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Responses of soil nitrous oxide production and abundances and composition of associated microbial communities to nitrogen and water amendment - Qing Wang; Yu-Rong Liu; Cui-Jing Zhang; Li-Mei Zhang; Li-Li Han; Ju-Pei Shen; Ji-Zheng He (Biology and Fertility of Soils, 2017)

Effect of long-term industrial waste effluent pollution on soil enzyme activities and bacterial community composition - Gangavarapu Subrahmanyam; Ju-Pei Shen; Yu-Rong Liu; Gattupalli Archana; Li-Mei Zhang (Environmental Monitoring and Assessment, 2016)

Comparison of SPE, IFE, and FLC in Monitoring Patients with Multiple Myeloma After Autologous Stem Cell Transplantation - Wei Li; Jia-Zi Zhou; Hui-Rong Chang; Li-Jun Dai; Zi-Ling Zhu; Yu-Feng Feng; Fei-Ran Gong; De-Pei Wu (Cell Biochemistry and Biophysics, 2015)

Communities of gamasid mites on Eothenomys miletus in southwest China - Pei-Ying Peng; Xian-Guo Guo; Wen-Yu Song; Peng Hou; Yun-Ji Zou; Rong Fan; Xue-Song He (Biologia, 2015)

Expression of a gene encoding a rice RING zinc-finger protein, OsRZFP34, enhances stomata opening - Kuo-Hsuan Hsu; Chia-Chin Liu; Shaw-Jye Wu; Ying-Yu Kuo; Chung-An Lu; Ching-Rong Wu; Pei-Jyun Lian; Chwan-Yang Hong; Yi-Ting Ke; Juin-Hua Huang; Ching-Hui Yeh (Plant Molecular Biology, 2014)

Differential expression patterns and a novel interaction factor of Damaged DNA Binding Protein 1A (DDB1A) and DDB1B in Arabidopsis thaliana - Pei Hou; Peng-fei Ren; De-er Zeng; Gui-rong Yu; Wei Tang; Xu Zheng; Jian-ping Yang; Yongsheng Liu (Journal of Plant Biology, 2014)

Response of ammonia-oxidizing archaea and bacteria to long-term industrial effluent-polluted soils, Gujarat, Western India - Gangavarapu Subrahmanyam; Ju-Pei Shen; Yu-Rong Liu; Gattupalli Archana; Ji-Zheng He (Environmental Monitoring and Assessment, 2014)

Manganese concentrations in maternal–infant blood and birth weight - Limei Chen; Guodong Ding; Yu Gao; Pei Wang; Rong Shi; Hong Huang; Ying Tian (Environmental Science and Pollution Research, 2014)

Enhanced Oxidation Stability of Quasi Core-Shell Alloyed CdSeS Quantum Dots Prepared Through Aqueous Microwave Synthesis Technique - Hong-Ju Zhan; Pei-Jiang Zhou; Rong Ma; Xi-Jing Liu; Yu-Ning He; Chuan-Yun Zhou (Journal of Fluorescence, 2014)

Application of Endobronchial Ultrasound-Guided Transbronchial Needle Aspiration in the Management of Mediastinal and Hilar Lymphadenopathy Without Intrapulmonary Mass: Experience from the Largest Cancer Center of Southern China - Guang-yu Luo; Pei-qiang Cai; Jie-hua He; Jian-jun Li; Yin Li; Hong-bo Shan; Rong Zhang; Xiao-yan Gao; Xiang-ming Lao; Guo-liang Xu (Cell Biochemistry and Biophysics, 2013)

Discovery of a novel esterase subfamily sharing an identified arm sequence (ArmEst) by gene-specific metagenomic PCR - Ao Zhang; Rong Zhao; Peng Jin; Lifang Ma; Xiaolong Xiong; Tian Xie; Xiaolin Pei; Li Yu; Xiaopu Yin; Qiuyan Wang (Biotechnology Letters, 2013)

Tectonic mechanism of the Suining (Ms5.0) earthquake, center of Sichuan Basin, China - Rong-jun Zhou; Yong Li; Laurence Svirchev; Yong-jiu Zhang; Deng-fa He; Yu-lin He; Pei-lin Zhao; Zan-jun Wang; Feng Long; Jin-rong Su; Shi-yuan Wang; Ming-jian Liang; et al. (Journal of Mountain Science, 2013)

Magma mingling and chemical diffusion in the Taojiang granitoids in the Hunan Province, China: evidences from petrography, geochronology and geochemistry - Kai-Xing Wang; Pei-Rong Chen; Wei-Feng Chen; Hong-Fei Ling; Kui-Dong Zhao; Zhi-Qiang Yu (Mineralogy and Petrology, 2012)

Association of thyroglobulin gene variants with carcass and meat quality traits in beef cattle - Guan-Yu Hou; Zheng-Rong Yuan; Han-Lin Zhou; Lu-Pei Zhang; Jun-Ya Li; Xue Gao; Dong-Jing Wang; Hui-Jiang Gao; Shang-Zhong Xu (Molecular Biology Reports, 2011)

Effects of mercury on the activity and community composition of soil ammonia oxidizers - Yu-Rong Liu; Yuan-Ming Zheng; Ju-Pei Shen; Li-Mei Zhang; Ji-Zheng He (Environmental Science and Pollution Research, 2010)

Detection of expression of influenza virus receptors in tissues of BALB/c mice by histochemistry - Zhang-Yong Ning; Min-Yi Luo; Wen-Bao Qi; Bo Yu; Pei-Rong Jiao; Ming Liao (Veterinary Research Communications, 2009)

Human signal peptide had advantage over mouse in secretory expression - Xue-wu Xu; Shu-jun Pei; Xue-rong Miao; Wei-feng Yu (Histochemistry and Cell Biology, 2009)

Reactions of 3-benzoyl-7-dimethylamino-4-hydroxycoumarin and their potential applications in solution- and solid-phase synthesis - Pei-Yu Kuo; Rong-Ren Chuang; Ding-Yah Yang (Molecular Diversity, 2009)

Erratum: Cloning and sequencing of the phycocyanin gene from Spirulina maxima and its evolutionary analysis - Ping Yu; Jian-Rong Li; Pei-Lin Cen; Song Qin; Fan Lin (Journal of Applied Phycology, 2003)

Cloning and sequencing of the phycocyanin gene from Spirulina maxima and its evolutionary analysis - Ping Yu; Jian-Rong Li; Pei-Lin Cen (Journal of Applied Phycology, 2002)

GSTP1 polymorphisms and gastric cancer in a high-risk Chinese population - Veronica Wendy Setiawan; Zuo-Feng Zhang; Guo-Pei Yu; Qing-Yi Lu; Yong-Liang Li; Ming-Lan Lu; Ming-Rong Wang; Chun Hua Guo; Shun-Zhang Yu; Robert C Kurtz; Chung-Cheng Hsieh (Cancer Causes & Control, 2001)